Strategic HR management and building of international teams as a strategy for global competitiveness - Rachwal-Mueller, A.; Рахвал-Мюллер, А. (Харківський національний автомобільно-дорожній університет, 2024)
Strategic HR management is changing rapidly to address new challenges and issues in today's global marketplace. This paper explores the latest theories and trends in the field, provides insights into the role of cross-cultural competence in strategic HR management, and consequently the importance of aligning HR practices with overall business strategy and building of international teams. It highlights the importance of aligning HR practices with overall business strategy and building international teams. The aim is to underscore the significance of cross-cultural competence across various HR fields and to advocate for its development among HR professionals to enhance organizational performance in the global marketplace. Drawing from a breadth of scholarly work, it underscores the necessity for HR professionals and researchers to stay abreast of current trends and theories in the field. Research indicates that strategic HR management and international team-building require a deep understanding of cultural differences and the ability to manage and leverage diversity. Cross-cultural competence plays a crucial role in various HR fields, including workforce planning and talent acquisition, learning and development, employee relations, succession planning, and diversity and inclusion. The paper emphasizes the significance of cross-cultural competence in each of these areas, highlighting the need to understand cultural nuances, adapt HR practices, and promote inclusivity. By developing cross-cultural competencies, HR professionals can attract, retain, and develop talent from diverse cultural backgrounds, enhancing organizational performance in the global marketplace. A brief methodology description and literature review for further research and discussion proposal is proposed. In conclusion, the article underscores the pivotal role of cross-cultural competence in strategic HR management and advocates for continued research and exploration in this domain to enhance organizational performance and competitive advantage in the global arena.
Стратегічне управління людськими ресурсами та формування міжнародних команд як стратегія для глобальної конкурентоспроможності
Keywords: strategic HR management; cross-cultural competencies; global competitiveness; diversity; inclusion; international teams; стратегічне управління людськими ресурсами; міжкультурні компетенції; глобальна конкурентоспроможність; різноманіття; інклюзивність; міжнародні команди; 303.7:316.72:659.22; 10.30977/ЕТК.2225-2304.2024.43.157